Simultaneous determination of iron (II) and iron (III) via flow injection analysis (FIA) - optimization of FIA manifold / Zainiharyati Mohd Zain, Rohana Atan and Mohd Noor Mokhtar - Mohd Zain, Zainiharyati; Atan, Rohana; Mokhtar, Mohd Noor (2006)
A reversed flow injection analysis (rFIA) method has been developed for the sequential determination of iron species based on the multi wavelength detection of the l,10-phenantroline-Fe(II) complex (X,max = 512 nm) and 2,2'-azino-bis(ethylbenzthiazoline-6-sulfonic acid)(ABTS)-Fe(III) complex (Xmax = 418 nm). Optimum FIA conditions including concentration of ligand reagents, length of reaction coil, flow rate and reagent volume were established. The proposed method was successfully applied for the determination of iron (II) and iron (III) in standard mixtures and iron tablets. The results for total iron were found to be in good agreement with those obtained by manual atomic absorption spectrometric method.